CRIMES AGAINST HUMANITY: THE CHARACTERISTICS OF KOSOVO AND RWANDA VICTIMS - LÓPEZ-PALAFOX, JUAN; GARCÍA-GARCÍA, ABEL; LÓPEZ-RODRÍGUEZ, ÁLVARO; LARA-LÓPEZ, PATRICIA; DIEGO, RAFAEL GÓMEZ-DE; CHAMORRO-PETRONACCI, CINTIA; PÉREZ-SAYÁNS, MARIO (Innovare Journal of Social Sciences, 2020)
Objective: Crimes occurred in Rwanda (1994) and Kosovo (1999) have been considered as genocides. Our main objective was to describe the difference between the crimes committed in Kosovo and Rwanda based on the victims found in each area according to their age, gender, and way to die. Methods: Bodies were found in those places selected by field observers. We have included all human and material elements that were found near the bodies in Rwanda and Kosovo. We also have taken photographs to the lesions in some cases to document our findings. As a criterion for inclusion, it was necessary to be able to identify the form of death and the ethnic group (in Rwanda, Tutsi or moderate Hutus, and in Kosovo, the Kosovar Albanian victims). All samples that did not meet the requirements to determine personal characteristics were excluded. Results: A total of 1044 bodies were individually studied, 857 from Rwanda and 187 from Kosovo. Our results reveal differences in the injuries presented in most Rwandan victims, were most were due to machetes or canes, and those in Kosovo where most were due to firearms or explosions. Most of the bodies studied in Rwanda belong to the Tutsi ethnic group and were not buried. However, the majority of the bodies found in Kosovo were individually buried. Conclusions: We conclude that there are differences in the studied victims attending to their characteristic and their wounds in Kosovo and Rwanda.